Carrion´s disease during pregnancy presenting with acute respiratory distress and multi organ failure. A case report - Zegarra Piérola, Jaime (2020)
Carrion´s disease is an endemic disease in Peru caused by Bartonella bacilliformis presenting with an acute or hemolytic form and a chronic verrucous form with asymptomatic bacteremia. The acute form is usually serious and is associated with high morbidity and mortality. We report the case of a case of a young pregnant woman from Yungay, Ancash who presented with the acute form complicated with multi organ failure and acute respiratory distress syndrome needing mechanical ventilation and dying.